Growth Rate and Biomass Leaf Production Of Thalassia hemprichii at Pengudang and Dompak Waters, Bintan Island - Afis Irawan; Fadhliyah Idris; Aditya Hikmat Nugraha (Faculty of Agriculture Musamus University, 2021)
Research on the rate of growth and reproduction of seagrass leaf type Thalassia hemprichii has been done in Pengudang and Dompak Waters, Bintan Island. Aim this research for compare the growth rate and biomass production of Thalassia hemprichii in the waters of Pengudang and Dompak, Bintan Island. The research was done by purposive sampling method, 30 seagrass leaves samples were taken using a plot measuring 50x50 centimeters. The results of the study were in the growth value of the seagrass leaf type Thalassia hemprichii in the waters of Pengudang and Dompak 1.03 mm/day and 0.77 mm/day. Reproduction of the biomass leaves of the seagrass type Thalassia hemprichii 2.12 gDW/m2 and 0.80 gDW/m2, the density of seagrass type Thalassia hemprichii 119.22 stands/m2 and 96.00 stands/m2. Based on test Two-Way ANOVA. There is no noticeable difference between the growth and production of the type of seagrass leaves Thalassia hemprichii in the waters of Pengudang and Dompak, Bintan Island.